Fallacies, irrelevant facts, and myths in the discussion of capital regulation: Why bank equity is not socially expensive - Anat R. Admati; Peter M. DeMarzo; Martin Hellwig; Paul Pfleiderer (Max Planck Institute for Research on Collective Goods, 2013)
We examine the pervasive view that 'equity is expensive' which leads to claims that high capital requirements are costly for society and would affect credit markets adversely. We find that arguments made to support this view are fallacious, irrelevant to the policy debate by confusing private and social costs, or very weak. For example, the return on equity contains a risk premium that must go down if banks have more equity. It is thus incorrect to assume that the required return on equity remains fixed as capital requirements increase. It is also incorrect to translate higher taxes paid by banks to a social cost. Policies that subsidize debt and indirectly penalize equity through taxes and implicit guarantees are distortive. And while debts informational insensitivity may provide valuable liquidity, increased capital (and reduced leverage) can enhance this benefit. Finally, suggestions that high leverage serves a necessary disciplining role are based on inadequate theory lacking empirical support. We conclude that bank equity is not socially expensive, and that high leverage at the levels allowed, for example, by the Basel III agreement is not necessary for banks to perform all their socially valuable functions and likely makes banking inefficient. Better capitalized banks suffer fewer distortions in lending decisions and would perform better. The fact that banks choose high leverage does not imply that this is socially optimal. Except for government subsidies and viewed from an ex ante perspective, high leverage may not even be privately optimal for banks. Setting equity requirements significantly higher than the levels currently proposed would entail large social benefits and minimal, if any, social costs. Approaches based on equity dominate alternatives, including contingent capital. To achieve better capitalization quickly and efficiently and prevent disruption to lending, regulators must actively control equity payouts and issuance. If remaining challenges are addressed, capital regulation can be a powerful tool for enhancing the role of banks in the economy.
Keywords: G21; G28; G32; G38; H81; K23; 330; capital regulation; financial institutions; capital structure; "too big to fail"; systemic risk; bank equity; contingent capital; Basel; market discipline